Integrating Emotions and Cognition Throughout the Lifespan - Labouvie-Vief, Gisela (Springer International Publishing : Imprint: Springer, 2015)
This book presents a coherent framework for the balanced development of emotions and cognition throughout the lifespan. It synthesizes rich sources across psychology and neuroscience to show that the brain is hard-wired for basic emotions as well as reasoning, and that these structures mature as individuals learn social rules in interactions with others and progress through complex relationships. In contrast to traditional views that held emotions and cognition to be opposing domains, the author builds on recent views that emphasize the ideal of a cooperative relationship among the two domains. Central to this construct is the fragile balance of expansion and stability that is crucial to both cognitive and affective development: how it can be nurtured for optimal functioning, and how, in contrast,  the absence of such a caring context functions to derail growth and encourage  pathology that can be carried into later stages of the lifespan. This groundbreaking volume: Traces historical changes in conceptions of the relation between reason and emotion from ancient philosophy to modern science. Expands on Piaget's theories of alternating phases of equilibrium in cognitive development and details how these contribute toward integrated cognitive-emotional growth. Discusses neurobiological mechanisms contributing to balance between emotional and cognitive development. Presents examples of the integration of cognitive/emotional development from infancy to adulthood. Explores the relationships between affect and cognition in later life. Integrating Emotions and Cognition Throughout the Lifespan is an essential resource for researchers, graduate students, and clinicians in a range of disciplines, including developmental psychology, aging, educational philosophy, biological psychology, and personality/social psychology.  .